2000
DOI: 10.1073/pnas.220203197
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine–didanosine coexposure potentiates DNA incorporation of zidovudine and mutagenesis in human cells

Abstract: Drug combinations that include nucleoside reverse transcriptase inhibitors (NRTIs) are remarkably effective in preventing maternalviral transmission of HIV during pregnancy. However, there may be potential long-term risks for children exposed in utero. Examination of the genotoxic and mutagenic effects of two NRTIs, zidovudine [AZT (3-azido-3-deoxythymidine)] and didanosine [ddI (2,3-dideoxyinosine)], in cultured human lymphoblastoid cells revealed multiplicative synergistic enhancement of AZT-DNA incorporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 30 publications
6
41
0
3
Order By: Relevance
“…Therefore, we cannot conclude with certainty that the elevated reticulocyte micronucleus frequencies observed in ZDV-exposed infants in our study will be associated with a higher risk of future disease in these infants compared with healthy, non-exposed individuals. However, we are concerned about the long-term health implications for these infants because the MN increases noted in this study add to the growing body of evidence that ZDV readily induces genetic damage (mutational and clastogenic) in both nuclear and mitochondrial DNA in a variety of in vitro and in vivo test systems (Sussman et al, 1999;Poirier et al, 2004;Chan et al, in press;Von Tunglen et al, 2004;Meng et al, 2002;Olivero et al, 2002;Bishop et al, 2004;Witt et al, 2004;Meng et al, 2000;Hong et al, in press;Olivero, in press). …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, we cannot conclude with certainty that the elevated reticulocyte micronucleus frequencies observed in ZDV-exposed infants in our study will be associated with a higher risk of future disease in these infants compared with healthy, non-exposed individuals. However, we are concerned about the long-term health implications for these infants because the MN increases noted in this study add to the growing body of evidence that ZDV readily induces genetic damage (mutational and clastogenic) in both nuclear and mitochondrial DNA in a variety of in vitro and in vivo test systems (Sussman et al, 1999;Poirier et al, 2004;Chan et al, in press;Von Tunglen et al, 2004;Meng et al, 2002;Olivero et al, 2002;Bishop et al, 2004;Witt et al, 2004;Meng et al, 2000;Hong et al, in press;Olivero, in press). …”
Section: Discussionmentioning
confidence: 89%
“…First, DNA incorporation of ZDV and resulting genetic effects may be enhanced by the presence of additional nucleoside analogues such as lamivudine or didanosine (Meng et al, 2002;Bishop et al, 2004;Witt et al, 2004;Meng et al, 2000), although neither of these two nucleosides alone induces micronuclei in mice (Phillips et al, 1991;Von Tungeln et al, 2004;Witt et al, 2004;Von Tungeln et al, 2002;Von Tungeln et al, in press). All women in this study who received ZDV during the prenatal period also received lamivudine, whereas infants received ZDV alone during postpartum treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no clear knowledge of the direct or indirect consequences of exposure to this complex regimen in the human fetus, studies in cell culture and animal models suggest increased genotoxicity is induced by the combination. In vitro studies revealed a synergistic effect on the frequency of HPRT and TK mutants induced by the AZT-ddI combination as compared with single drug exposures [28]. Similarly, an additive effect was observed in the incorporation of AZT into DNA of E. patas monkeys exposed in utero to AZT and 3TC during the last period of their gestation [15].…”
Section: Combined Therapymentioning
confidence: 86%
“…As with AZT 5¢-triphosphate, ddA 5¢-triphosphate inhibits viral reverse transcriptase and is incorporated into viral DNA (Faulds and Brogden, 1992); it is also possible that ddA 5¢-triphosphate becomes incorporated into mammalian DNA (Faulds and Brogden, 1992). Meng et al (2000) have examined the genotoxic and mutagenic effects of AZT and ddI in TK6 human lymphoblastoid cells. At equimolar concentrations, ddI was considerably more cytotoxic than AZT, as measured by cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…These toxicities appear to be a consequence of inhibiting mitochondrial DNA polymerase g with a resultant impairment of mitochondrial enzyme synthesis and oxidative phosphorylation (Carr and Cooper, 2000). ddI also appears to potentiate the mutagenicity of AZT because when human TK6 lymphoblastoid cells were incubated with AZT, ddI or a mixture of AZT and ddI, the combination of AZT and ddI increased the incorporation of AZT into cellular DNA and the mutant frequency within the hypoxanthine-guanine phosphoribosyltransferase (HPRT) and thymidine kinase (TK) genes (Meng et al, 2000). The increase in mutant frequency was attributed to an increase in point mutations (Meng et al, 2002).…”
mentioning
confidence: 99%